World politics since 1945 - Calvocoressi, Peter (Routledge, 2009)
The ninth edition of this enormously successful standard work has been expanded to take into account the developments of the last 10 years, including the wars in Iraq, Afghanistan, and Sudan; the accelerating emergence of India and China as major powers; the major political developments in Latin America, including the rise and perhaps fall of Chavez in Venezuela; the march of globalisation and the popular protest movements against; the expansion eastwards of the European Union; instability in the Middle East and the question of oil and energy supply.